Foreign Direct Investment in the New European Union Member States and Developing Countries of Asia under Conditions of the Global Financial and Economic Crisis: Comparative Aspects - Witkowska, Janina (Comparative Economic Research. Central and Eastern Europe, 2010)
The objective of this article is a comparative analysis of the changing position of new European Union member states and the developing countries of Asia in global and regional FDI flows as well as an assessment of the impact of the global crisis on the position of these regions and selected countries in terms of FDI. The analysis encompasses European Union member states that received membership as a part of the enlargement of 2004 and 2007 as well as the developing sub–regions of Asia—i.e. East, South-East, and South Asia. The conducted analysis demonstrates that the position of the developing countries of Asia is significantly stronger than that of the new European Union member states, which is mainly determined by the scale of the economies of countries such as China and India. Subject to conditions of global crisis, Asia and Oceania as a whole noted growth in the inflow of FDI in 2008 by almost 17%, where the European Union member states saw a 2% fall. The situation inside the analyzed regions is extremely varied in terms of noticeable effects of the crisis in the FDI sphere. It is dependent on not only processes of economic growth, but also on the character of investments made in the individual countries and sub– regions as well as motives behind the actions of investors.